Accounting Transparency, Fear Sentiment and the COVID-19 Epidemic: For Public Health Security and the Construction of an Early Warning System - Wang, Haiyan; Sun, Min; Li, Han; Kang, Diantong; Yan, Lei; Gao, Jianhao (Frontiers in Public Health, 2022)
A central issue of public health security early warning system is to establish a set of responsibility-oriented incentives and restraint mechanisms. This is closely related to the accounting transparency of the institutional environment and the fear sentiment of the individual predicament. This study analyses the relationship between accounting transparency, fear sentiment, and COVID-19 through VAR model analysis, and the results show that: Firstly,we find a significant and negative relationship between accounting transparency and the daily new COVID-19 patients. In particular, accounting transparency has a negative impact on the increase in the number of people infected with a two-period lag, while, the three-period lag in the number of new epidemics has a negative impact on accounting information. Secondly, accounting transparency has a positive impact on the increase in the search popularity on COVID-19 within a three-period lag. While after the three-period lag in the number of new epidemics has a positive impact on accounting information. Thirdly, an increase in fear sentiment can be driven by fear of COVID-19. Fourthly，in the public health early warning system, according to the above-mentioned time characteristics, the system arranges the emotional counselling, early warning incentives and institutional constraints to be dealt with in the first four days. In addition, in the early warning target-oriented system setting, the parallel system helps to improve the early warning efficiency.